Efektivitas Edukasi Interaktif Terhadap Peningkatan Pengetahuan Siswa tentang Anti-Bullying: The Effectiveness of Interactive Education in Improving Students’ Knowledge on Anti-Bullying - Syahruddin, Muh.; Gunawan, Gunawan; Adi, Krisna; Pasaribu, Nico Saputra; Feratiwi, Feratiwi; Nurkhadijah, Nurkhadijah; Hafsah, Hafsah; Sania, Sania; Munadirah, Munadirah; Febrianti, Fani; Valentina, Ana; Paradilla, Dista (Chakra Brahmanda Lentera Institute, 2026)
Bullying is a common problem among elementary school students and may negatively affect their psychological well-being and learning process. Interactive education has the potential to improve students' knowledge and awareness regarding bullying prevention. This study aimed to evaluate the effectiveness of interactive education in improving students' knowledge of anti-bullying. A pre-experimental study with a one-group pretest-posttest design was conducted involving 42 sixth-grade students at SD Negeri 1 19 Nopember, Kolaka Regency. The intervention consisted of interactive educational sessions including participatory lectures, group discussions, educational videos, PowerPoint presentations, and anti-bullying posters. Students' knowledge was assessed using a 10-item questionnaire before and after the intervention. Data were analyzed descriptively using mean scores and knowledge-level distribution. The mean knowledge score increased from 6.45 ± 3.21 before the intervention to 7.81 ± 2.80 after the intervention. Following the educational program, 19% of students demonstrated a high level of knowledge, 45% had a moderate level, and 36% remained in the low category. Most students were able to identify the definition and impacts of bullying and recognized the importance of reporting bullying incidents, although some still experienced difficulty distinguishing different types of bullying. Interactive education effectively improved elementary school students' knowledge and awareness regarding bullying prevention. This approach may serve as an effective school-based health promotion strategy to prevent bullying. Establishing a school anti-bullying team or organization is recommended to sustain bullying prevention efforts.